Law Enforcement and the Task of Prosecution in the Covid-19 Pandemic - Burhanuddin, Sanitiar (Lex Publica, 2021)
The Covid-19 pandemic has had a significant impact on people’s lives. Many people were forced to lose their jobs due to the layoffs carried out by several factories. Almost all people were restricted in their movements, which made it difficult for their economy and led to difficulties in meeting their basic daily needs. It causes some people to commit crimes to make ends meet and their families. The state of the people’s economy, which has not returned to its maximum as before the Covid-19 pandemic, has given rise to crime and corruption, which continue to occur daily. Therefore, there is a need for a settlement in tackling various crimes that law enforcers must uphold in dealing with criminal acts of corruption and street crimes. In this paper, the author uses the normative juridical method. The author examines matters relating to digital disruption in the law enforcement process at the judiciary during the Covid-19 pandemic. The authors conducted a literature study to support this method by analyzing secondary data from primary and secondary legal materials. From the research that the author conducted, the authors obtained several factors that motivated a person to commit crimes during the Covid-19 pandemic, including economic factors, the social environment, the scene, and the consequences of crimes in other places also triggered the perpetrators to move. In addition to these crimes, this country also has problems in law enforcement that are less than optimal due to online trials. Therefore, the government continues to regulate regulations to prevent the spread of Covid-19 and enforce the law as effectively as possible, despite several obstacles to its implementation. Abstrak Pandemi Covid-19 menimbulkan dampak signifikan terhadap kehidupan masyarakat. Banyak masyarakat yang terpaksa harus kehilangan pekerjaan akibat pemberhentian yang dilakukan oleh sejumlah pabrik, dan hampir seluruh masyarakat terbatasi geraknya sehingga menyulitkan perekonomian mereka dan berujung pada kesulitan dalam pemenuhan kebutuhan pokok sehari-hari. Hal ini menyebabkan sebagian orang melakukan tindak kejahatan untuk mencukupi kebutuhan hidupnya dan keluarga. Keadaan perekonomian masyarakat yang belum kembali maksimal sebagaimana sebelum pandemi Covid-19 menimbulkan kejahatan dan korupsi yang semakin hari terus terjadi. Maka dari itu perlunya suatu penyelesaian dalam menanggulangi berbagai kejahatan yang harus ditegakkan oleh penegak hukum dalam menghadapi tindak pidana korupsi dan kejahatan jalanan. Dalam tulisan ini penulis menggunakan metode yuridis normatif. Penulis meneliti hal-hal yang menyangkut wujud disrupsi digital dalam proses penegakan hukum di lembaga kejaksaan pada masa pandemi Covid-19. Untuk mendukung metode ini penulis melakukan studi kepustakaan dengan menganalisis data sekunder berupa bahan hukum primer dan bahan hukum sekunder. Dari telaah yang penulis lakukan penulis mendapatkan beberapa faktor yang menjadi pendorong seseorang melakukan kejahatan di masa pandemi covid-19, di antaranya: faktor ekonomi, lingkungan sosial, tempat kejadian, dan juga akibat kejahatan-kejahatan di tempat lain yang ikut memicu tergeraknya pelaku. Selain tindak kejahatan tersebut, negeri ini juga memiliki problem dalam penegakan hukum yang kurang maksimal akibat dari persidangan secara online. Maka dari itu pemerintah terus mengatur regulasi, peraturan-peraturan dalam upaya mencegah perluasan covid-19 serta tetap melakukan penegakan hukum seefektif mungkin, meskipun terdapat beberapa hambatan dalam pelaksanaannya. Kata kunci: Penegakan Hukum, Lembaga Penegak Hukum, Covid-19